PERAN TOKOH WANITA PADA MASA KOLONIALISME - Aah Syafaah (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2017)
AbstractThe idea of Shrieke in his race theory, as quoted by Azra, says that the Portuguese expansion can not be separated from the Crusade War in Europe and the Middle East. It is further said that the desire of adventure and ambition of honor combined with religious spirit is the driving force that drives the expansion of the Portuguese into the Asian region. The arrival of the Portuguese came in early 1511 to Malacca, followed by other Europeans such as France, Britain and the Netherlands to various parts of the archipelago, ultimately creating resistance from the people of the archipelago. In an effort to defend his honor and his homeland, the indigenous fighters were not only from the Adam people, as some of them were heroes of the female sex. The colonial period and the effort to achieve independence are very difficult times to pass. Where at that moment, words no longer sounded but only the sounds of ammunition. This is certainly a difficult time especially for women. In this condition, they are required to maintain the honor and salvation of their own lives.Keywords: female, colonial, Islamization